2006
DOI: 10.1056/nejmoa052627
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Surgery to Reduce the Risk of Gynecologic Cancers in the Lynch Syndrome

Abstract: These findings suggest that prophylactic hysterectomy with bilateral salpingo-oophorectomy is an effective strategy for preventing endometrial and ovarian cancer in women with the Lynch syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
454
0
17

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 707 publications
(475 citation statements)
references
References 24 publications
(1 reference statement)
4
454
0
17
Order By: Relevance
“…With increasing use of molecular screening and efficient prevention of cancer in families undergoing surveillance, present and future generations in Lynch syndrome families are likely to experience less cancer. Our findings suggest that extended information on the natural history of Lynch syndrome may be required to motivate individuals in such families for genetic testing and participation in surveillance programs [17,18]. Experiences from routine examinations of patients with colorectal and endometrial cancer suggest that, although family history and analysis of tumor tissue suggested Lynch syndrome, only 1 in 5 patients made an appointment with a genetic counsellor [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…With increasing use of molecular screening and efficient prevention of cancer in families undergoing surveillance, present and future generations in Lynch syndrome families are likely to experience less cancer. Our findings suggest that extended information on the natural history of Lynch syndrome may be required to motivate individuals in such families for genetic testing and participation in surveillance programs [17,18]. Experiences from routine examinations of patients with colorectal and endometrial cancer suggest that, although family history and analysis of tumor tissue suggested Lynch syndrome, only 1 in 5 patients made an appointment with a genetic counsellor [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Enrollment in specialised registries and attendance at familial, high-risk gastrointestinal cancer clinics can facilitate the long-term care of such patients Vasen et al, 2014). There is no role for prophylactic colectomy, but prophylactic hysterectomy and bilateral salpingo-oophorectomy should be considered in women who have completed childbearing or after age 40 years as it significantly reduces the risk of both endometrial and ovarian cancer (Schmeler et al, 2006;Vasen et al, 2013). Recommended surveillance includes: colonoscopy every 1-2 years starting at age 25 (or 5 years younger than the youngest affected family member if <30 years), 2 yearly upper endoscopy starting age 30 in families with gastric cancer or at high ethnic risk.…”
Section: Rev Ised Bethesda Guidelinesmentioning
confidence: 99%
“…28 Prophylactic hysterectomy and oophorectomy is recommended by some after completed childbearing but before natural menopause, although evidence from randomised trials are lacking. 5,29,30 Screening for endometrial cancer in the general population is not recommended.…”
Section: Etiology and Risk Factorsmentioning
confidence: 99%